PREDIKSI EROSI DAN SEDIMENTASI DI SUB DAERAH ALIRAN SUNGAI KEDUANG KABUPATEN WONOGIRI - Joko Sutrisno; Bunasor Sanim; Asep Saefuddin; Santun R.P. Sitorus (Media Konservasi, 2011)
Land resources management at Keduang Sub-Watershed will be influence of environment quality, physic (erosion, sedimentation, debit of Keduang River), chemistry (water quality) and socio economic aspect. This research aim to know the level of erosion and sedimentation that happened in Keduang Sub-Watershed, Wonogiri Regency. Research method which is used is descriptive. Data types which are obtained are secondary data from Centre of Research and Development Technology of Watershed Management, Forestry Department, BPS-Statistic of Wonogiri Regency and Agriculture Department of Wonogiri Regency. Method of  analysis’s data which is used in this research is Universal Soil Loss Equation (USLE) Method to predict the soil erosion. Results of this research are: the level of erosion in Keduang Sub-Watershed is 44 ton/ha/year or 1,9 million ton/year. The sediment yield from Keduang Sub-Watershed to Wonogiri Basin equal 164.000 ton/year. Keywords : land resources management, erosion, sedimentation, USLE.